Mechanisms of steam turbine blade particle erosion and crucial parameters for minimizing blade erosion. (August 2013) - Wang, Shun-sen; Cai, Liu-xi; Mao, Jing-ru; Zhang, Jun-jie; Xu, Ya-tao
Reducing the solid particle erosion of blades is crucial to increasing the service life, reliability and cost of steam turbines. In this article, we performed many three-dimensional numerical simulations on the trajectory and erosion of solid particles in turbine cascades, and the relationship between the structural parameters of cascades and erosion characteristics was systematically studied. The results indicated that the erosion damage to the blade depends mainly on the first impingement of every solid particle on the wall after entering into the cascades, and the erosion rate of the first impingement is much larger than that caused by additional impingements on the wall after rebounding of the particle. Furthermore, it was also found that the structure parameter G = ( by − t )/ bx of the cascade and the attack angle ( α ) of the steam admission are the most important parameters of blade erosion resistance. Increasing G or α would shift the position of the particle's first impingement toward the leading edge of the blade. The most effective way of increasing the erosion resistance of the blade is to select an appropriate G while considering the particle size and attack angle ( α ) required to prevent ferric oxide particles from causing serious erosion on the trailing edge. All of these achievements are important in the blade selection and anti-solid particle erosion optimization processes when designing a new turbine or upgrading an old turbine.